The Relationship between Sustainable Entrepreneurship and Sustainable Innovation toward the Sustainable Competitiveness of Fertilizer Products A3N 766HI from the Landfill Waste Water Treatment Pakusari Jember throughout motivation for sustainable growth as a Result of the Programs' Campus - Silalahi, Amin (Proceedings of International Conference of Graduate School on Sustainability, 2023)
The aims of the study is to see there is or no relationship between Sustainable Entrepreneurship (SE) and Sustainable Innovation (SI) toward Sustainable Competitiveness (SC) of Fertilizer Products A3N 766HI from the Landfill Waste Water Treatment Pakusari Jember (LWWTPJ) athroughout motivation for sustainable growths as the result of the Programs' Independent' Campus and Learning (PICL). The research's questions namely: 1. Is there a relationship between SE and SI variables toward the Motivation for Sustainable (MfS) for model 1 and SE, SI toward SC throughthe MfS of A3N 766HI fertilizer products from the LWWTPJ as a result of the programs' campus independent and learning? 2. Is there stronger relationship between model one (SE, SI MfS) and model two (SE, SI and MfS SC of A3N 766HI fertilizer products from reservoir from LWWTPJ from the results of the programs independent' campus and learning? The research design is quantitative research and the data collection's method by questionnaires' instrument, distributed to 89 respondents. The instrument is also being tested with validity and reliability. Using the hypothesis testing is because to have a conclusion research. The results of this study are as the following: 1. The R-square value model 1 is 0.480 or 48% and the R-square value model two is 0.680 or 68% 2. There is no correlation stronger between the two models because F-square < F-table.